The parent trap [videorecording (DVD)] - Quaid, Dennis; Richardson, Natasha; Lohan, Lindsay, 1986-; Meyers, Nancy (Disney DVD : distributed by Buena Vista Home Entertainment, 2005)
An updated version of the 1961 Disney classic about separated identical twins. Hallie and Annie meet accidentally at camp and decide to reunite their divorced parents.